An Integrated Loop Model of Corrective Feedback and Oral English Learning: A Case of International Students in the United States - Lee, Eun Jeong (Esther) (Journal of International Students, 2018)
The author in this study introduces an integrated corrective feedback (CF) loop to schematize the interplay between CF and independent practice in L2 oral English learning among advanced-level adult ESL students. The CF loop integrates insights from the Interaction, Output, and Noticing Hypotheses to show how CF can help or harm L2 learners’ English practice routines. This study used a mixed method design, and the data for the CF loop were collected via qualitative open-ended survey questions and a set of forty student interviews. In the aggregate, interviewees describe a similar practice pattern and learning process and learning trajectory using their teachers’ oral CF, and cite common themes and reasons for whether teachers’ oral CF works or not.